Hermeneutics in the Development of Humanities and Religious Sciences: Models, Development and Research Methods. - Huda, Ali Anhar Syi'bul; Jannah , Miftahul; Nurfadilah, Utami; Nurhuda, Abid; Ansori, Inamul Hasan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
This research aims to describe the description of hermeneutics as a model of scientific research, development of humanities sciences, and as a research method in religious sciences. The method used is a literature study with a qualitative approach. Then analyzed descriptively. The results of the research show that hermeneutics emerged a long time ago during ancient Greek civilization and was more dominant in activities in understanding the holy scriptures, but in its development, it could reach the humanities and religious sciences. Apart from that, it also acts as a bridge to bring together hermeneutical theory with qualitative empirical research as well as symbols that are difficult for humans to understand in the phenomena of the universe. Therefore, the science of hermeneutics can interpret and express the meaning of texts by considering the social, cultural, and historical context. And of course, this is very useful in uncovering Divine messages through scripture texts which still need explanation so that you don't misapply God's teachings.